Early Diagnosis Expert System Hepatitis Using Naive Bayes Method: Early Diagnosis Expert System Hepatitis Using Naive Bayes Method - Gilang Irfansyah; Ucuk Darusallam; Benrahman Benrahman (Institute of Computer Science (IOCS), 2020)
Public health activities for the control of viral hepatitis have increased during the last three decades. In 2010, there is growing public awareness about the public health burden of viral hepatitis. However, there are major gaps in the response and increased mortality. Five virus responsible for most cases of viral hepatitis are hepatitis A, B, C, D, and E. All hepatitis viruses can cause acute hepatitis. However, only HBV, HCV and HDV frequent cause of chronic hepatitis, which can cause progressive scarring of the liver and primary liver cancer. Of these, HBV and HCV causes 96% of deaths from hepatitis virus, So the need for special treatment for hepatitis, with the creation of an expert system for diagnosis of hepatitis using Naive Bayes method that aims to diagnose the onset of hepatitis disease is expected to help users who still lay on knowledge as well as related information from hepatitis. Based on test results using 10 samples of data to get the value of accuracy of 90%. Ketikakuratan 10% is due at the time of the calculation method that uses a Naive Bayes highest value for the results obtained and if the same value system will take the value of the list of the first order for the results to a user